Microbial Enzyme Extract Evaluation for Calcium Carbonate Biocementation: Implications for Ground Improvement - Daryono, Lutfian Rusdi; M Akmal Putera; Tomohiko Abe; Aoi Ichinohe; Kazunori Nakashima; Satoru Kawasaki (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Microbially Induced Carbonate Precipitation (MICP) has emerged as a promising technique for slope surface stabilization or other ground improvements. However, its effectiveness in fine-grained soils is limited due to challenges associated with bacterial cell transport. This study explores the feasibility of an alternative approach Enzyme Induced Carbonate Precipitation (EICP) from microbial bacteria itself for stabilizing fine-grained slope soils. In this study, urease was extracted from whole-cell cultures of Lysinibacillus xylanilyticus (LyXy) which developed under Hokkaido University and using cyclic sonication. The extracted enzyme solution was then applied to a precipitation test using fine-grained sand and/or soil samples. The performance of enzyme extract was evaluated in comparison to traditional MICP with a focus on the adaptability to precipitate the fine-grained sand/soil and the effectiveness of the enzyme. Results indicated that the urease extract exhibited higher enzymatic activity than the original bacterial culture and maintained better stability at 15°C. The observation verified that the effectiveness of enzyme-induced and MICP would vary depending on the soil to be treated. The enzyme-induced resulted in unconfined compressive strength around 4 MPa and deeper cementation in the finest sand. Microscopic analysis revealed that while enzyme-induced produced smaller calcium carbonate crystals compared to MICP, it generated a significantly higher quantity of crystals, leading to enhanced particle bonding and improved soil stabilization.